Continuous and embedded learning for organizations - Quigley, Jon M.; Quigley, Shawn P. (Boca Raton, FL : CRC Press, Taylor & Francis, 2020)
There is considerable connection between growth of the personnel in the organization and the ability for the company to compete over time.Looking outside for help training may be required but looking within for opportunities for enhanced training andgrowth, will foster a continually improving and growing organization. This book examines the opportunities for learning, within the organization and its' activities, along with the connection to motivation. Additionally, it provides information on the characteristics of organizations that are able to quickly disseminate, along with approaches for improving this distribution of that learning throughout the organization.
OCLC-licensed vendor bibliographic record.
Keywords: Employees -- Training of; Continuing education; Organizational learning; Career development; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Project Management; COMPUTERS / Information Technology